Odpowiedzi

Najlepsza Odpowiedź!
2010-01-09T20:09:57+01:00
(√5 - √3)(√5+√3)=5-3=2

(√ 7 + 4)( 4 +√ 7)=(4-√ 7)(4+√ 7)=16-7=9

(√11+ 2)(11- 2)=11√11-2√11+22-4=9√11+18

(2√2 - 1)( 2√2 +1)=4*2-1=8-1=7

(√15 - √6)(√5 - √2)=√75-√30-√30+√12=5√3-2√15+2√3=7√3-2√15

(√20 - √18)(√20 + √18)=20-18=2

2010-01-09T20:14:36+01:00
A) 5-3=2
b) 7+4√7+4√7+16=23+8√7
c)11√11+22-2√11-4=9√11+18
d)8-1=7
e)
f)
2010-01-09T20:17:14+01:00
A) (√5 - √3)(√5+√3)= 5 + √15 - √15 - 3 = 2
b) (√ 7 + 4)( 4 +√ 7)= 4√7 + 7 +16 + 4√7= 8√7 + 23
c) (√11+ 2)(11- 2)= 11√11 - 2√11 + 22 - 4= 9√11 + 18 = 9(√11 + 2)
d) (2√2 - 1)( 2√2 +1)= 8 + 2√2 - 2√2 - 1= 7
e) (√15 - √6)(√5 - √2) = √75 - √30 - √30 + √12 = 5√3 - 2√30 + 2√3 = 7√3 - 2√30
f) (√20 - √18)(√20 + √18)= 20 + √360 - √360 - 18= 2